EVALUATION OF THE FEASIBILITY AND ACCEPTABILITY OF AN EDUCATIONAL INTERVENTION IN NURSING: PROTOCOL OF A PILOT STUDY - Nuno Miguel dos Santos Martins Peixoto; Tiago André dos Santos Martins Peixoto; Candida Assunção Santos Pinto; Célia Samarina Vilaça de Brito Santos (Universidade Federal do Paraná, 2023)
Objective: to explain the protocol of a pilot study that aims to evaluate the feasibility and acceptability of a nursing educational intervention to promote health behaviors in cancer survivors. Method: the protocol was developed based on the Standard Protocol Items: Recommendations for Interventional Trials 2013 - SPIRIT 2013 Statement, in Porto, Portugal in 2022. Results: the protocol would support the implementation of the pilot study in order to assess the feasibility and acceptability of the procedures defined for the intervention, estimate the recruitment and retention of participants, and define the sample size so that possible reformulations of the educational intervention could be considered and proceed to the evaluation phase. Conclusion: this study has laid the structural foundations and content for conducting a pilot study and may later influence the decision to conduct a randomized controlled trial.